2016
DOI: 10.1248/bpb.b16-00094
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid Ameliorated Diabetic Nephropathy by Attenuating Hyperglycemia-Mediated Oxidative Stress

Abstract: Oxidative stress has a great role in diabetes and diabetes induced organ damage. Endoplasmic reticulum (ER) stress is involved in the onset of diabetic nephropathy. We hypothesize that ER stress inhibition could protect against kidney injury through anti-oxidative effects. To test whether block ER stress could attenuate oxidative stress and improve diabetic nephropathy in vivo and in vitro, the effect of ursodeoxycholic acid (UDCA), an ER stress inhibitor, on spontaneous diabetic nephropathy db/db mice, ER str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Oxidative stress is a significant pathogenesis of DN, as oxidative phosphorylation of mitochondria in the kidney produces large amounts of reactive oxygen species (ROS), which ultimately affect kidney structure and physiological function [27,28]. Recent studies have confirmed that hyperglycemia-induced oxidative stress is closely related to mesangial cell and podocyte injuries, as well as interstitial fibrosis [29]. Rodent experiments have shown that antioxidant therapies can inhibit the occurrence of DN, and herbal extracts with antioxidant effects can inhibit glomerular hypertrophy and improve renal function [30].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a significant pathogenesis of DN, as oxidative phosphorylation of mitochondria in the kidney produces large amounts of reactive oxygen species (ROS), which ultimately affect kidney structure and physiological function [27,28]. Recent studies have confirmed that hyperglycemia-induced oxidative stress is closely related to mesangial cell and podocyte injuries, as well as interstitial fibrosis [29]. Rodent experiments have shown that antioxidant therapies can inhibit the occurrence of DN, and herbal extracts with antioxidant effects can inhibit glomerular hypertrophy and improve renal function [30].…”
Section: Discussionmentioning
confidence: 99%
“…ROS levels are regulated by endogenous antioxidants and antioxidases including GSH and SOD, which indirectly reflects the body’s ability to clear ROS. SOD1 and SOD3 was downregulated in diabetic rats [25]. MDA, an end-product of lipid peroxidation, directly reflect the extent of lipid peroxidation [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to Table 1, available evidences support that activation of Nrf2/ARE pathway not only attenuates high glucose-induced podocyte [82, 92, 112, 113], endothelium [71, 76], and mesangial cell [73, 86, 91, 97, 101, 103, 105, 107] injury in glomeruli but also alleviates renal tubular cell [72, 80, 81, 98, 99] damage. In addition, sulforaphane [85, 86, 89, 96] and resveratrol [74, 84, 87, 97, 101] are the most well-studied ones among those Nrf2 activators.…”
Section: Role Of Nrf2/are Pathway In Dn: Evidences In Basic Researchmentioning
confidence: 99%